FAKTOR INDIVIDU CHIEF EXECUTIVE OFFICER TERHADAP CAPITAL STRUCTURE DECISION PADA PERUSAHAAN YANG TERDAFTAR DALAM LQ45 DI BURSA EFEK INDONESIA - Thomas Yulianto Prakoso; Putu Anom Mahadwartha; Arif Herlambang (CALYPTRA, 2018)
his study aims to analyze the effect of Chief Executive Officer (CEO) individual factor towards capital structure decision using Leverage as a dependend variable with Age (CEO Age), Tenure as independenvariable amd Capex, ROA (Return on Asset), dan IO (Institutional Ownership) as control variable on LQ45 companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2016. This research uses quantitative approach with single regression analysis model. This study uses sample of firms which are listed on LQ45 in IDX on 2012 - 2016. The number of final samples used in this study were 66 business entities with 330 observations.The study findings suggest that Age and ROA variables have negative and significant effect towards Leverage, while Tenure and IO variable have positive and significant effect towards Leverage. On the other hand, Capexvariables does not indicate significant effect towards Leverage in LQ45companies on the period 2012-2016.